Dynamic Relationship among Effective Supply Chain Practices, Income, Exchange Rate, Foreign Direct Investment, and Export Performance - Nguyen Thi Viet Nga; Giang Ngoc Long; Giang Ngoc Ha Linh (International Journal of Supply Chain Management, 2020)
This study has an effort to explore the dynamic relationship among income, exchange rate, foreign direct investment, effective supply chain practices and export performance. Based on quarterly data from Q2/2009 to Q4/2019, constituting 43 observations. To attain dynamic and unvarying relationship among these variables, applying Vector Autoregressive Model, results indicate that, in short run, each variable is highly influenced by changes of value and past value of its and the other variables at different degree. In addition, there does not exist a long run association among exchange rate, income, foreign direct investment and export in Vietnam in the research period.